Care and social suffering: nursing within contexts of political violence - Arias Lopez, Beatriz Elena (Investigación y Educación en Enfermería, 2025)
<!-- [if gte mso 9]> <![endif]--> In light of the armed conflict and political violence in Colombia, the contribution of nursing professionals is fundamental in caring for individuals, families, and communities, whose experience because of these types of events has been devastating, not only for their physical health, but for their psychic and emotional stability. Due to this, we give way to some brief considerations on the armed conflict and political violence in Colombia. Thereafter, the notion of social suffering is included as a perspective that broadens the horizon of care within this context, then we review the elements that characterize the perspectives and domains of nursing and the possibilities offered by the new epistemological tendencies to reflect on life, as a central focus of care, from the proposals by Afaif Meleis; and, finally we discuss the role of nursing professionals in the restitution of the dignity of those who have experienced the consequences of the armed conflict. <!-- [if gte mso 9]> Normal 0 21 false false false ES-CO X-NONE X-NONE <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]-->